Integrated care in Germany – a stony but necessary road! - Volker Amelung (International Journal of Integrated Care, 2012)
German healthcare provides a very comprehensive benefits catalogue, high quality standards, low access barriers and in particular healthcare which is independent from one's income. But at the same time it is one of the most expensive systems in the world. Reasons for the high costs of care are mainly due to the separation of the outpatient, inpatient and rehabilitation sectors, the poor information flow between the service providers and insufficient competition in healthcare provision. In the last 15 years the German government has introduced various reform acts and in doing so has followed a continual path of development: more competition for care concepts between health insurances, more options for the insured and more leeway for players in the various sectors of healthcare. The following article gives an overview of new forms of contracting that have been introduced and provides recommendations for the further development of integrated care in the German healthcare system.